Linguistic evidence of in-group bias in English and Spanish Wikipedia articles about international conflicts. (June 2020) - Álvarez, Guadalupe; Oeberst, Aileen; Cress, Ulrike; Ferrari, Laura
Highlights: English and Spanish Wikipedia articles about international conflicts are analyzed. Appraisal analysis is used to examine in-group bias in Wikipedia articles. Important associations are shown between engagement resources and in-group bias in Wikipedia. Bias in Wikipedia seems to be usually expressed implicitly rather than explicitly. Abstract: The aim of this study is to identify linguistic categories which could be bias indicators in both English and Spanish versions of Wikipedia articles about international conflicts. In this sense, Appraisal analysis -particularly, engagement- is used to examine whether the articles are biased in favor of a group (in-group bias). In the present study, only two kinds of these resources are focused: attribution and counter . The hypothesis we are discussing is that, in these articles, engagement categories serve as linguistic indicators of in-group bias. The analysis shows important associations between engagement resources and in-group bias. The findings seem to confirm that bias is usually expressed implicitly rather than explicitly.